Pope John Paul II’s Teaching and Gestures: The Influence on Polish-Jewish Reconciliation - Wawrzyńska-Furman, Luiza A. (The Copernicus Journal of Political Studies, 2018)
In the article, the author presents the influence of the theological teaching and symbolic gestures of Pope John Paul II on the Polish-Jewish reconciliation. Considering the main papal acts related to the Jewish community and Judaism, such as visiting the Great Synagogue of Rome, the apostolic visit to Israel (especially his visit to the Yad Vashem Institute and praying near the Western Wall), the establishment of diplomatic relations between the Holy See and the State of Israel, visiting the former Nazi concentration camp in Auschwitz-Birkenau, and his act of repentance on 12 March 2000. She presents the possible influence of the Roman Catholic Church on the change of Polish attitudes towards Jews. She also explains how the personal testimony of the Holocaust affected the Pope’s actions and opinions, and presents his teaching as innovative, post-Shoah theological doctrine, which changed the Holy See’s policy as well. The author presents John Paul II not only as an influential religious leader, significant theologian, and ethicist, but also as a politician and moral authority for Poles, who set the example for possessing a friendly attitude in relations with Jews and Israel, and recognized them as elder brothers in faith, and condemning all acts of anti-Semitism or anti-Judaism, which even today is accepted and justified by some of Poles. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14761